2023
DOI: 10.1039/d2cp04583d
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of direct Z-scheme triazine-based g-C3N4/BiOI (001) heterostructures: a hybrid density functional investigation

Abstract: In this work, we systematically investigate the photocatalytic mechanism of g-C3N4/BiOI (001) through hybrid functional calculations based on a first-principle theory. The staggered band structure is observed in the g-C3N4/BiOI...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…The BiOX(010) (X = Cl, I) facet has only one stoichiometric surface termination with strong stability, 27 while BiOX(001) facet has three kinds of terminations with different stabilities. 27 Kong et al 28 and Jing et al 29 and our previous investigations 30,31 have demonstrated that the 1X-terminated BiOX(001) (X = Cl, I) surface exhibits much lower surface energy than 2X-terminated BiOX(001) and BiO-terminated BiOX(001) surfaces, and the electronic structure of the 1X-terminated BiOX(001) surface is very similar to that of the bulk. 28–31 Therefore, it is reasonable to consider the BiOX(010) and 1X-terminated BiOX(001) (X = Cl, I) surfaces to construct the specific crystal facet combination interface models with the (001) and (010) facets of BiOCl and BiOI.…”
Section: Resultsmentioning
confidence: 78%
“…The BiOX(010) (X = Cl, I) facet has only one stoichiometric surface termination with strong stability, 27 while BiOX(001) facet has three kinds of terminations with different stabilities. 27 Kong et al 28 and Jing et al 29 and our previous investigations 30,31 have demonstrated that the 1X-terminated BiOX(001) (X = Cl, I) surface exhibits much lower surface energy than 2X-terminated BiOX(001) and BiO-terminated BiOX(001) surfaces, and the electronic structure of the 1X-terminated BiOX(001) surface is very similar to that of the bulk. 28–31 Therefore, it is reasonable to consider the BiOX(010) and 1X-terminated BiOX(001) (X = Cl, I) surfaces to construct the specific crystal facet combination interface models with the (001) and (010) facets of BiOCl and BiOI.…”
Section: Resultsmentioning
confidence: 78%
“…The (001) facet was also mainly investigated both experimentally [59,60] and theoretically [61,62] and is easiest to be exposed in practice [63]. There are three different terminations in the (001) facet, and the 1I-terminated (001) facet (a surface termination for the first layer with I and the subsurface layer with Bi) is the most stable and easiest to expose in experiments [26,64,65]. Therefore, the optimized Bi 2 WO 6 and BiOI unit cells are cleaved along the (001) direction with these terminations.…”
Section: Geometric Structures Of the Heterostructure Modelsmentioning
confidence: 99%
“…By combining the projected band structures and charge transfer mode, the band alignments of Bi 2 WO 6 (DL-O-Bi)/ BiOI(1I), Bi 2 WO 6 (O-Bi)/BiOI(1I), and Bi 2 WO 6 (O-W)/ BiOI(1I) are shown in figures 6(a), (c) and (e), respectively, in contrast to the vacuum level [26,64]. We are delighted to observe that figure 6(a) exhibits a distinct S-scheme character [34,35] in Bi 2 WO 6 (DL-O-Bi)/BiOI(1I), implying superior photocatalytic performance.…”
Section: Electronic Structures Band Alignments and Optical Absorption...mentioning
confidence: 99%
See 2 more Smart Citations